STRATEGI BIMBINGAN KELOMPOK MASYARAKAT MELALUI PERAN PENYULUHAN MEDIA ISLAM DALAM KEGIATAN KULTUM MENJELANG IFTAR PADA BULAN RAMADHAN - Duwi Mila; Muhammad Rifa'i Subhi (Universitas Muhammadiyah Metro, 2024)
Kultum activities leading up to iftar in the month of Ramadhan are an important moment in the lives of Muslim communities, which are often supported by the use of Islamic media as a means of religious outreach. However, the effectiveness of the group guidance strategy through Islamic media outreach in this activity still needs to be further evaluated. This research aims to evaluate the effectiveness of group guidance strategies through Islamic media counseling in cultural activities leading up to iftar, with a focus on increasing understanding, changing behavior and congregation satisfaction. This research uses a qualitative literature study approach. The evaluation shows that the group guidance strategy through Islamic media counseling in cultural activities leading up to iftar has a significant impact in increasing religious understanding, strengthening spiritual values, and producing positive behavioral changes in the Muslim community. Factors such as content quality, interaction between instructors and congregations, and social and cultural context play an important role in determining the effectiveness of this strategy. By paying attention to these aspects, this strategy can be an effective instrument in increasing the faith and quality of life of Muslim communities during the month of Ramadhan.